A randomized 500-subject open-label phase 3 clinical trial of minimally invasive surgery plus alteplase in intracerebral hemorrhage evacuation (MISTIE III). Issue 5 (July 2019) - Ziai, Wendy C; McBee, Nichol; Lane, Karen; Lees, Kennedy R; Dawson, Jesse; Vespa, Paul; Thompson, Richard E; Mendelow, A David; Kase, Carlos S; Carhuapoma, J Ricardo; Thompson, Carol B; Mayo, Steven W; et al.
Rationale and hypothesis: Surgical removal of spontaneous intracerebral hemorrhage may reduce secondary destruction of brain tissue. However, large surgical trials of craniotomy have not demonstrated definitive improvement in clinical outcomes. Minimally invasive surgery may limit surgical tissue injury, and recent evidence supports testing these approaches in large clinical trials. Methods and design: MISTIE III is an investigator-initiated multicenter, randomized, open-label phase 3 study investigating whether minimally invasive clot evacuation with thrombolysis improves functional outcomes at 365 days compared to conservative management. Patients with supratentorial intracerebral hemorrhage clot volume ≥ 30 mL, confirmed by imaging within 24 h ofknown symptom onset, and intact brainstem reflexes were screened with a stability computed tomography scan at least 6 h after diagnostic scan. Patients who met clinical and imaging criteria (no ongoing coagulopathy; no suspicion of aneurysm, arteriovenous malformation, or any other vascular anomaly; and stable hematoma size on consecutive scans) were randomized to either minimally invasive surgery plus thrombolysis or medical therapy. The sample size of 500 was based on findings of a phase 2 study. Study outcomes: The primary outcome measure is dichotomized modified Rankin Scale 0–3 vs. 4–6 at 365 days adjusting for severity variables. Clinical secondary outcomes include dichotomized extended Glasgow Outcome Scale and all-cause mortality at 365 days; rate and extent of parenchymal blood clot removal; patient disposition at 365 days; efficacy at 180 days; type and intensity of ICU management; and quality of life measures. Safety was assessed at 30 days and throughout the study.